Master Programme in Urban Conservation and Planning (Yildiz Technical University) - Galland, Daniel; Perić, Ana; Finka, Maroš (AESOP, 2020)
The Master Programme in Urban Conservation and Planning delivered at the Yildiz Technical University is recognised as a study programme focused on the historic preservation, yet with a distinctive consideration of both management and implementation-oriented approach in addressing the topic of conservation planning. It brings together the following aspects of quality in planning education: Programme Curriculum and Identity • A pragmatic approach, i.e. the focus on implementation measures in a specific context, and not solely on the general principles of conservation. • Acknowledgment of professional ethics through different topics relevant to urban conservation (e.g. disinvestment/decay, pressures of gentrification, • displacement, large scale urban projects, including infrastructure investments, tourism development and dilemmas of keeping the authentic character) in relation to specified conceptual themes (e.g. sustainability, rights-based approaches in urban conservation, reduction of poverty, resilience). • A well-interlinked and content-coordinated system of subjects aimed at enabling a balance between planning issues and specific topics of urban • conservation. Principles of Pedagogy • Advanced models for providing the students with a broad research competence – from the basic skills for conducting fundamental research to those inherent in applied research and the dissemination of research results. • Best practice examples of student/alumni/employer’s engagement by enabling its members to develop stronger relations with the university’s community, find mentorship and gain access to new professional networks. • Stimulation of the studio project as a tool for practical reasoning and practical judgement. Strengthening active and independent learning through an array of diverse student tasks (essays, seminars, studio work, thesis).
Yildiz Technical University 41.029236811800125, 28.888951825801524 https://ror.org/0547yzj13